Effectiveness of Implementation of Individual Counseling Services in Schools in Increasing Student Resilience - Liza Murni Susanti; Yarmis Syukur (Universitas Negeri Padang, 2021)
This research is motivated by the existence of various problems of students who need resilienceskills in order to be able to face these various problems such as not wanting to get along due to bullying, feeling they have no future due to having a broken home and there are some students who are lazy to study because of their low scores. To overcome these problems, individual counseling services are needed in order to increase student resilience so that students are able to deal with various problems in the right way. This study aims to describe the effectiveness of the implementation of individual counseling services in increasing student resilience based on the BMB3 aspects, namely thinking, feeling, behaving, acting and being responsible.This type of research is a descriptive quantitative type. The research subjects were 62 students of SMP Negeri 13 Padang who had resilience problems and had conducted individual counseling with BK teachers at school. The data collection technique used a questionnaire with a Likert scale model. Data were analyzed using descriptive statistical techniques.This study describes the effectiveness of individual counseling services in the high category in the high category. Based on the BMB3 aspect, namely, (1) the thinking aspect, is in the high category (40.3%); (2) the feeling aspect is in the high category (40.3%); (3) attitude aspect is in the high category (48.4%); (4) the acting aspect is in the high enough category (48.4%) and (5) the responsible aspect of students is in the high category (51.6%).